Late Diagnosis of Transaldolase Deficiency in an Adult Male with Hypergonadotropic Hypogonadism - Razak, Mohamed Tareq Al Abdul; Almazrouei, Raya (Journal of Diabetes and Endocrine Practice, 2025)
Transaldolase deficiency is a rare autosomal recessive disorder of the pentose phosphate pathway, most often recognized in infancy or early childhood due to severe hepatic or hematologic manifestations. We describe the case of a 33-year-old man whose diagnosis emerged only in adulthood, following a prolonged and fragmented journey across multiple specialties. His presentation included hypergonadotrophic hypogonadism, persistent cytopenias, splenomegaly, and subtle but persistent cardiac anomalies. The eventual diagnosis was secured through genetic testing, which identified a homozygous pathogenic variant in the TALDO1 gene. This case highlights that transaldolase deficiency may manifest beyond childhood with insidious, multisystem involvement. It underscores the critical value of coupling meticulous clinical observation with targeted genetic testing in unveiling rare but clinically meaningful diagnoses.
Keywords: transaldolase deficiency; pentose phosphate pathway; inborn errors of metabolism; hypergonadotrophic hypogonadism; homozygous mutation; genetic